2013
DOI: 10.1016/j.jpedsurg.2013.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary support on Day 30 as a predictor of morbidity and mortality in congenital diaphragmatic hernia

Abstract: Purpose Congenital diaphragmatic hernia (CDH) is associated with significant in-hospital mortality, morbidity and length-of-stay (LOS). We hypothesized that the degree of pulmonary support on hospital day-30 may predict in-hospital mortality, LOS, and discharge oxygen needs and could be useful for risk prediction and counseling. Methods 862 patients in the CDH Study Group registry with a LOS≥30 days were analyzed (2007–2010). Pulmonary support was defined as (1) room-air (n=320) (2) noninvasive supplementati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 23 publications
2
8
0
Order By: Relevance
“…(27) Our previous analysis of the CDHSG registry found that pulmonary support (PS) on DOL-30 is the greatest predictor of inpatient mortality, length-of-stay and short-term pulmonary morbidity. (10) In the present study we found that PS on DOL-30 is also a strong independent predictor of longer-term outcomes, including pulmonary and developmental morbidity at both 1 and 5 years of age. Similar to our previous analysis, we again noted that PS on DOL-30 is a good summary indicator for the severity of pulmonary disease and highly correlated with most other predictors of outcome.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…(27) Our previous analysis of the CDHSG registry found that pulmonary support (PS) on DOL-30 is the greatest predictor of inpatient mortality, length-of-stay and short-term pulmonary morbidity. (10) In the present study we found that PS on DOL-30 is also a strong independent predictor of longer-term outcomes, including pulmonary and developmental morbidity at both 1 and 5 years of age. Similar to our previous analysis, we again noted that PS on DOL-30 is a good summary indicator for the severity of pulmonary disease and highly correlated with most other predictors of outcome.…”
Section: Discussionsupporting
confidence: 65%
“…Similar to our previous analysis, we again noted that PS on DOL-30 is a good summary indicator for the severity of pulmonary disease and highly correlated with most other predictors of outcome. (9, 10) We found that PS on DOL-30 was a stronger independent predictor of long-term morbidities than either defect size or presence of a V/Q mismatch. Taken together with the previous analyses of the CDHSG registry, we believe that the degree of pulmonary support on DOL-30 may be used as a simple cross-institutional tool to identify patients with a higher risk of long-term morbidity.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…These agents are often ineffective making extracorporeal membrane oxygenation therapy (ECMO) the only therapeutic option to stabilize hemodynamics. Published studies from the CDH registry report a 27-35% (8,9) ECMO utilization rate, making alternate therapies that may be more effective in the setting of refractory hypotension essential. Two recent case reports describe the efficacy of terlipressin, an arginine vasopressin analogue, in the setting of hemodynamic instability in CDH (7,10).…”
mentioning
confidence: 99%
“…Long-term follow-up of CDH in Canada, however, appears more variable and may be influenced by centre volume, with larger centres having interdisciplinary follow-up clinics and smaller centres providing decentralized surveillance through local pediatric surgeons and subspecialty pediatricians. 78 In addition to regular surveillance, we recommend intensified screening for patients identified as high risk, which includes those requiring pulmonary support at 30 days of age, 79 who need patch repair 80 and who need extracorporeal life support. 81 These CDH survivors should be offered screening (e.g., growth, hearing), including standardized neurodevelopmental testing.…”
Section: C-ld)mentioning
confidence: 99%